Customs and culture of Okinawa - Zabilka, Gladys (Charles E. Tutte Company, 1959)
The material in this book was originally used as a guide for the hundreds of boys or girls attending the American schools on the military base of Okinawa. Until the easter Sunday invasion in the year 1945, very little was known of this Pacific island of the Far East. Since then, Americans have palyed an important part in its reconstruction, and this book was compliled to further thier understanding of tyhis island civilization and its people and customs.